Mechanisms of Cancerprotective Effects of Phytosterols. Literature Review - I. R. Rakhmatullina; N. V. Kudashkina; V. Yu. Frolova; M. Kh. Ozieva; B. I. Sadykov (Креативная хирургия и онкология)
Cancer is recognized as the second leading cause of mortality in the Russian Federation. Prolonging the life of oncology patients involves treatment with toxic drugs, causing multiple side effects. Today, scientists around the world are striving to find non-toxic drugs. The present study explores phytosterols. Phytosterols refer to a class of steroids widely distributed in plants as an essential component of plant cell membranes. They include stigmasterol, beta-sitosterol, and campesterol. Stigmasterol has been found to increase the expression of proapoptotic genes (Bax, p53) and decrease the expression of the antiapoptotic gene Bcl-2 in HepG2 liver cancer cells. Stigmasterol is able to induce cell arrest in G0-G1 phase (stationary phase), resulting in fewer cells in the G2/M phase (division phase). It induces apoptosis and protective autophagy in gastric cancer cells while inhibiting the Akt/mTOR signaling pathway. β-sitosterol exhibits growth inhibitory and cytotoxic effects against a number of established cancer cell lines in vitro and in vivo, and remains free from acute/subacute toxic effects. β-sitosterol is widely used to treat chronic prostate diseases. In 2020, spendings on dietary supplements rich in beta-sitosterol accounted for $24 827 065 in the USA. Campesterol induces cell apoptosis via the mitochondrial pathway. It appears cytotoxic to U937 hepatocellular cancer cells. Campesterol induces cell apoptosis and activates proapoptotic signaling in ovarian cancer cell lines of a person. The present literature review demonstrates that specific substances in this group, beta-sitosterol, stigmasterol, and campesterol, provide pronounced antitumor effects.